Effect of borderline amniotic fluid index in last trimester on perinatal outcome in eastern India: a prospective observational study - Sharma, Meeta; Gupta, Shagun; Kothari, Aarti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: This study was done to evaluate the impact of borderline amniotic fluid index (AFI) on perinatal outcomes in term pregnancies. Methods: This prospective observational study was conducted between January and June 2024. A total of 120 pregnant women at term (37-40 weeks) were divided into two groups: group A (n=60) with normal AFI (8-24 cm) and group B (n=60) with borderline AFI (5-8 cm). Participants were followed until delivery and up to 7 days postpartum with assessment of maternal and neonatal outcomes. Results: Baseline maternal characteristics were comparable between groups. The borderline AFI group had significantly higher rates of fetal distress requiring caesarean delivery (30.0% versus 13.3%, p=0.026), meconium-stained amniotic fluid (36.7% versus 16.7%, p=0.013), and NICU admissions (23.3% versus 10.0%, p=0.048). Neonates in the borderline AFI group had lower birth weights (3042±384g versus 3186±352g, p=0.034), lower umbilical cord pH (7.24±0.08 versus 7.28±0.07, p=0.004), and more early neonatal complications (18.3% versus 6.7%, p=0.045). Subgroup analysis revealed poorer outcomes in pregnancies with AFI 5-6.5 cm compared to AFI 6.6-8 cm. Conclusions: Borderline AFI at term is associated with adverse perinatal outcomes and should be considered a risk factor requiring closer antenatal monitoring and modified intrapartum management. The risk appears to increase with decreasing AFI values, even within the borderline range.